A organização e guarda dos itens bibliográficos nos acervos das bibliotecas visando a preservação, conservação e recuperação da informação - Fonseca, Daniel Milaneto (Universidade Federal de São Carlos, 2015)
ABSTRACT This paper aims to demonstrate the importance that libraries should give to the correct storage of bibliographic items in their collections, in order to increase the useful life of the items and facilitate their recovery. This paper will point out the main procedural errors committed in storage and suggest procedures that are best suited to meet this purpose. The importance of standardizing storage procedures and their usefulness will be shown not only in terms of conservation of items, but also in the recovery of information by users and in terms of library administration. Aspects such as: conservation, location, quality of materials, adequate and planned physical space, inventory, security of bibliographic items, behavior of professionals involved in storage, supervision of storage, thinning policy, marketing to users and guidance to users will be the main points addressed in this paper. Comparisons will be made between storage methods in order to demonstrate how neglecting bibliographic items can be potentially harmful not only to the collection itself, but also to the institution's image among its users and the community in general. We will seek to use the epistemology of the administration area to improve the flow of the storage process and the transmission of knowledge. The conclusion of the study allowed us to conclude that only with standardization, organization, strategy, adequate procedures, socialization and collaboration of all involved will we be able to transform our institutions into reliable information reference centers that are accessible to users in general.
The organization and storage of bibliographic items in library collections with a view to preserving, conserving and retrieving information
Keywords: Organização de acervos; Guarda de livros; Manual de guarda; Conservação; Preservação; Manual de guarda; Collection organisation; Collection preservation; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO